The Value Relevance of Financial Distress Risk in the Case of RASDAQ Companies - Ioan-Bogdan Robu; Mihaela-Alina Robu; Marilena Mironiuc; Florentina Olivia Balu (Journal of Accounting and Management Information Systems (JAMIS), 2014)
The financial distress risk concept has been referred as follow: negative net assets, insolvency, bond default, overdraft, unpaid dividends for the preferred stocks, bankruptcy etc. From all the stakeholders, investors are interested in the financial position and performance of a company and its ability to continue as a going concern, without knowing the appearance of financial distress status. The purpose of this study aims to test the value relevance of the appearance of distress risk on investors' decisions on the purchase or sale of stock, with impact on stock return, for the Romanian listed companies in RASDAQ section. In order to reach the objective, the study was carried on upon a sample of 70 Bucharest Stock Exchange (BSE) listed companies, between 2008 and 2014, using statistical methods like analysis of variance (ANOVA), simple linear regression and ANCOVA models. Through the obtained results, it was demonstrated the difference between financial distressed companies and performant companies and the influence of belonging to a company in the high risk category on the stock return.
Keywords: B23; C58; G14; G33; M41; 650; value relevance; distress risk; financial ratios; ANOVA; ANCOVA; RASDAQ